EDUKASI DAN PENDAMPINGAN TATA KELOLA SAMPAH BERKELANJUTAN MELALUI PENDEKATAN 3R DI BANK SAMPAH BARANANG SIANG KOTA BOGOR - Dwi Prasetyo; , Alfred O.M Dima; Refli Refli; Ida Nurwiana (Universitas Nusa Cendana, 2026)
Low public awareness and a limited waste disposal system are the main causes of environmental damage resulting from the accumulation of trash. This community service program was designed to address the issue of illegal dumping by implementing the 3R method (Reduce, Reuse, Recycle). This initiative aims to foster community self-reliance in waste management, improve environmental hygiene, and revitalize the local economy. The program was implemented in Baranang Siang Village, Bogor City, through outreach and periodic mentoring. The results of these activities demonstrate positive changes, as evidenced by increased public understanding and awareness of ideal waste management practices. Additionally, the program successfully initiated the formation of independent waste bank management groups to ensure the program’s sustainability. These waste banks play a crucial role, not only as facilities for sorting waste materials but also as catalysts for the circular economy by converting economically valuable inorganic waste into alternative income for residents. Through educational interventions and community capacity-building, this program has proven effective in changing residents’ behavior and creating a waste management system that is both financially and socially sustainable at the local level.